Adventures into the Unknown: Exploring the Lived Experience of East Asian International Students as Foreign Accented Speakers in Australian Higher Education - Park, Eunjae; Hodge, Steven; Klieve, Helen (Journal of International Students, 2021)
Second language (L2) international students are frequently blamed for miscommunication and even stigmatized and marginalized due to the way they sound. However, little is known about how their accent contributes to the L2 lived experience at foreign universities. Taking a mixed methods phenomenological approach, survey (N = 306) and semi-structured interviews with participants from East Asian countries (N = 5), this study reveals that their personal journey as foreign-accented speakers can be traced through a four-stage process: (a) surprise, (b) anticlimax, (c) learning to survive, and (d) feeling empowered. The first two themes are a period wherein participants experience high levels of stress and anxiety because of having to fit into new learning environments. The last two themes refer to a stage where they developed the ability to survive with increasing self-confidence. Practical implications for improving the campus climate for all L2 students are discussed.